Teaching through dance: An opportunity to introduce physically active academic lessons. (October 2021) - Beserra, Vagner; Nussbaum, Miguel; Navarrete, Monica; Alvares, Danilo
Abstract: Introducing physically active academic lessons into the school routine implies a significant change in educational practice. The aim of this study is to explore the acceptability and feasibility of delivering physically active academic lessons through dance. During five training sessions, 37 teachers created a series of dance routines based on mathematical functions. At the end, all teachers participated in focus groups. The results of the thematic analysis revealed high levels of interest among the teachers in incorporating physically active academic lessons into the school routine. Teachers also identified the main barriers to implementation and constructed lesson plans. Highlights: Teacher training raised awareness of the benefits of physically active academic lessons. Teachers identified opportunities to use physically active lessons in their own domains. Teachers identified the main barriers to implementation as those described in the literature.